Analysis of computer vision and image analysis technics - Rybchak, Z.; Basystiuk, O. (Commission of Motorization and Energetics in Agriculture, 2017)
Computer vision and image recognition are one of the most popular theme nowadays. Moreover, this technology developing really fast, so filed of usage increased. The main aims of this article are explain basic principles of this field and overview some interesting technologies that nowadays are widely used in computer vision and image recognition.
Keywords: computer vision; image recognition; object recognition; machine learning; computer with high-level understanding; digital images processing; scene reconstruction